SOCIOLINGUISTIC COMMUNICATIVE COMPETENCE OF EFL STUDENTS: SERIES OF FAMILY INTERACTION IN THE TIME OF ONLINE LEARNING - Andi Nurhikmah; Anugerah Febrian Syam; Sumrah AP (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
Given the prevalence of the Covid-19 pandemic and Indonesian higher education in carrying out learning from home (LFH), the present study aims at investigating how EFL students develop their communicative competence during family interaction. This study employs ethnographic study where the data was acquired though the duration of one academic semester during students’ LFH context. Furthermore, the present study observes how students’ family behave and communicate in relation to the students’ communicative competence viewing from Canale and Swain (1980) model. Online interview and internet social media documentation undertaken to strengthen the distant observation in collecting data on the differences in the way students’ family interact and communicate in relation to the students’ communicative competence and the extent to which the attitudes they perform in home setting. The results divided into two areas: interactions among family members who have the same level and interactions with respected family members. It was revealed that appropriateness and intimacy existed in the interactions carried out among family members who have the same level. Meanwhile, the interactions that occur between EFL students and their respected family members covers humble and enjoyable communication. It can be concluded that these types of interaction were based on the fact that EFL students have ample opportunities to build closeness due to the realization of learning from home and the dominant role of their home culture to all family members.